2015
DOI: 10.1155/2015/365604
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Weight Loss with Vagal Nerve Blockade but Not with Sham: 18-Month Results of the ReCharge Trial

Abstract: Background/Objectives. Vagal block therapy (vBloc) is effective for moderate to severe obesity at one year. Subjects/Methods. The ReCharge trial is a double-blind, randomized controlled clinical trial of 239 participants with body mass index (BMI) of 40 to 45 kg/m or 35 to 40 kg/m with one or more obesity-related conditions. Interventions were implantation of either vBloc or Sham devices and weight management counseling. Mixed models assessed percent excess weight loss (%EWL) and total weight loss (%TWL) in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 10 publications
0
59
0
Order By: Relevance
“…The effect of vBloc on weight loss in the ReCharge Trial has been previously reported up to 18 months [3, 6]. The estimated mean percentage of excess weight loss (%EWL) was 26 % (10 % total weight loss [%TWL]) for vBloc and 17 % (6 % TWL) for Sham at 12 months ( p  < 0.001).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The effect of vBloc on weight loss in the ReCharge Trial has been previously reported up to 18 months [3, 6]. The estimated mean percentage of excess weight loss (%EWL) was 26 % (10 % total weight loss [%TWL]) for vBloc and 17 % (6 % TWL) for Sham at 12 months ( p  < 0.001).…”
Section: Introductionmentioning
confidence: 88%
“…The study design and methods of the ReCharge Trial study have been described previously [3, 6]. The study participants were enrolled both in the USA (eight sites) and in Australia (two sites).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermittent blockade is hypothesized to avoid neural adaptation as occurred in the past with truncal vagatomy. A device for this purpose has been approved by the Food and Drug Administration 13 .…”
Section: Specific Bariatric Surgical Proceduresmentioning
confidence: 99%
“…Regarding gastrointestinal endoscopic devices, the literature looks promising but does not have long-term data 13 . Weight loss is modest while the device safety is good.…”
Section: Bariatric Surgery Safetymentioning
confidence: 99%